2019
DOI: 10.1128/jvi.01716-18
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mapping of Regions Involved in the Negative Imprinting of Virion Particle Infectivity and in Target Cell Protection by Interferon-Induced Transmembrane Protein 3 against HIV-1

Abstract: The interferon-induced transmembrane proteins (IFITMs) are a family of highly related antiviral factors that affect numerous viruses at two steps: in target cells by sequestering incoming viruses in endosomes and in producing cells by leading to the production of virions that package IFITMs and exhibit decreased infectivity. While most studies have focused on the former, little is known about the regulation of the negative imprinting of virion particle infectivity by IFITMs and about its relationship with targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 63 publications
4
35
0
Order By: Relevance
“…The cell and virion lysate were immunoblotted and infectivity of cell-free virions were measured on TZM-bl reporter cell line. Consistent with other studies [37, 40, 43], we did not observe any differential effects of Ptm IFITM expression on Env processing in the producer cells and Env incorporation into viral particles (S4A and S4B Fig). In addition, Ptm IFITM expression did not affect infectivity of SHIV virions produced during 48 hours in these experiments (S4C Fig).…”
Section: Resultssupporting
confidence: 93%
“…The cell and virion lysate were immunoblotted and infectivity of cell-free virions were measured on TZM-bl reporter cell line. Consistent with other studies [37, 40, 43], we did not observe any differential effects of Ptm IFITM expression on Env processing in the producer cells and Env incorporation into viral particles (S4A and S4B Fig). In addition, Ptm IFITM expression did not affect infectivity of SHIV virions produced during 48 hours in these experiments (S4C Fig).…”
Section: Resultssupporting
confidence: 93%
“…In addition to the protective function of IFITM proteins to reduce viral infection of host cells, IFITM proteins, particularly IFITM2 and 3, can lead to the production of virions that package IFITMs and display reduced entry into target cells (Compton et al, 2014; Tartour et al, 2014, 2017). One study found that IFITM proteins interact with HIV envelope protein in viral producer cells to disrupt envelope protein processing and virion incorporation, which impairs virion infectivity (Yu et al, 2015); however, another found that IFITM3 expression in producing cells did not affect the amount of envelope protein incorporation into progeny HIV-1 virions (Appourchaux et al, 2018). Both studies reported that the level of IFITM protein incorporation into progeny virions does not correlate with the extent of infectivity reduction.…”
Section: Ifitms Mainly Restrict Virus Infection At Cell Entrymentioning
confidence: 99%
“…More strikingly, deletion of C-terminal 12-aa or 18-aa converted IFITM1 to a potent enhancer of MERS-CoV and HCoV-OC43 entry (Zhao et al, 2014, 2018). A recent mutagenesis study indicated that amino acid residues 127–132 in the CTD domain of IFITM3 differentially modulates its activities in target cell protection and negative imprinting of progeny HIV-1 infectivity (Appourchaux et al, 2018). These studies clearly indicate that the CTD of IFITMs contains multiple structure motifs that regulate the subcellular localization and antiviral functions.…”
Section: Structural Function Relationship Of Ifitm Proteinsmentioning
confidence: 99%
“…Remarkably, IFITM proteins display a second layer of antiviral activity, which consists in diminishing the infectivity and fusogenicity of enveloped virus particles produced in IFITM protein-expressing cells (Compton et al, 2014, Tartour, Appourchaux et al, 2014. This process is often, but not always, accompanied by incorporation of IFITM proteins into the membrane of secreted virions (Appourchaux, Delpeuch et al, 2019). Future studies are required to characterize susceptibility of CHIKV particles to IFITM-mediated negative imprinting and whether the mode of viral counteraction identified in this study is related to this site of action rather than to entry inhibition.…”
Section: Discussionmentioning
confidence: 99%